Residual Chernobyl fallout and Sellafield pollutants found on the Isle of Man - McKenna, P.; Longworth, R.D. (The Science of the total environment, 1995)
The Isle of Man is particularly vulnerable to radioactive pollution being located in the middle of the Irish Sea, only 55 km from the Sellafield nuclear site. Paradoxically, radioactive fallout from the accident at Chernobyl is the only significant radioactive pollution on the Island and requires legal restrictions on sheep farming. This paper gives and overview of the occurrence and magnitude of radioactive pollution on the Isle of Man, using results of live-monitoring of the Island's hill flocks since August 1987, and data selected from the results of laboratory analysis of more than 1000 samples of foodstuffs and environmental materials between 1990 and 1993. Radioactive contamination is of no significance in local agricultural produce, however, about one sixth of the Island's hill grazing land is still subject to controls. Sellafield pollutants are found only in samples from the marine environment.